2016
DOI: 10.1186/s40779-016-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between smoking and the risk of acute mountain sickness: a meta-analysis of observational studies

Abstract: BackgroundPeople rapidly ascending to high altitudes (>2500 m) may suffer from acute mountain sickness (AMS). The association between smoking and AMS risk remains unclear. Therefore, we performed a meta-analysis to evaluate the association between smoking and AMS risk.MethodsThe association between smoking and AMS risk was determined according to predefined criteria established by our team. Meta-analysis was conducted according to the PRISMA guidelines. We included all relevant studies listed in the PubMed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Different selection criteria may lead to different results; we used strict inclusion criteria, high-quality studies, and control for confounding variables and heterogeneity by different methodological tools. Our meta-analysis results contrast with one meta-analysis [ 34 ] but accord with the other one [ 33 ]. Meta-analysis of 11 observational studies suggested an AMS incidence rate of 25.02%, being lower if the traveller climbed below 3500 MASL than if the traveller climbed higher than 3500 MASL.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Different selection criteria may lead to different results; we used strict inclusion criteria, high-quality studies, and control for confounding variables and heterogeneity by different methodological tools. Our meta-analysis results contrast with one meta-analysis [ 34 ] but accord with the other one [ 33 ]. Meta-analysis of 11 observational studies suggested an AMS incidence rate of 25.02%, being lower if the traveller climbed below 3500 MASL than if the traveller climbed higher than 3500 MASL.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies were systemically reviewed to explore the association between smoking and the risk of AMS because of the importance of this possible association in clinical practice and public health. To our knowledge, prior to our study, two meta-analyses explored the association between smoking and AMS [ 33 , 34 ] with different results. Vinnikov et al, 2016, found that smoking was not significantly associated with AMS (OR 0.88, 95% CI, 0.74 to 1.05) whereas Xu et al [ 34 ] found that smoking may protect against AMS development (OR 0.71, 95% CI, 0.52 to 0.96).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, individuals were taken to very high altitudes (above 4000 masl), and the authors described smoking as a protective factor for AMS (RR=0.76 and 0.55, respectively), as found in a meta-analysis by Xu et al (pooled OR=0.71, 95% CI 0.52 to 0.96). 17 However, Li et al , 21 and Vinnikov et al 22 found smoking to be a risk factor (RR=1.11 and HR=1.9, respectively) when studying occupational cohorts or climbers commuting to very high altitudes (above 4000 masl), results that were in line with those shown in the meta-analysis performed by Vinnikov et al (pooled OR=0.88, 95% CI 0.74 to 1.05). 23 …”
Section: Discussionmentioning
confidence: 52%
“… 12–15 Around 30% of the world’s population declare being active smokers, yet there is a notable lack of consensus regarding the relationship between smoking and AMS risk. A recent meta-analysis performed by Vinnikov et al 16 showed that there was no significant association between smoking and AMS, while another performed by Xu et al 17 found an association between smoking and AMS, the former being a protective factor. The smoking status of travellers is not routinely explored, potentially resulting in an incomplete or misguided approach in the pretravel advice and treatment they receive.…”
Section: Introductionmentioning
confidence: 97%